Digitalisasi Pencatatan Keuangan pada Usaha Coffee & Eatery BD Dubeskabta - Adrian Varino Geovanny; Aisya Syifa Safitri; Arzu Nafiputra; Daniella Dara Dewantomo; Gracialla Akhasya Raditoputri; Jocelyn Adrielle Santoso; Kezia Agatha; Patricia Audra Sului; Nurhayati Nurhayati (Pusat Pengabdian kepada Masyarakat (PPKM) Universitas Prasetiya Mulya, 2025)
This study explores the implementation of digital financial record-keeping at Coffee & Eatery BD Dubeskabta, a student-run MSME at SMKN 12 Kabupaten Tangerang, as part of the Community Development program by Universitas Prasetiya Mulya. Based on observations and interviews, the primary issue identified was the inefficiency and error-prone nature of manual bookkeeping. To address this, the team developed a Google Sheets-based system to automate profit, tax, and cash flow calculations. The training was conducted in three phases: a trial session (January 31, 2025), a main workshop (February 3, 2025), and subsequent monitoring. Post-implementation evaluation revealed improved efficiency and accuracy in financial recording, as well as enhanced ease for students in preparing financial reports. Despite some challenges related to mobile device data entry, the digital system proved more effective than manual methods. These findings support the integration of financial digitalization into vocational entrepreneurship curricula to strengthen students’ managerial competencies in business operations.